Hispidacine, an unusual 8,4′-oxyneolignan-alkaloid with vasorelaxant activity, and hispiloscine, an antiproliferative phenanthroindolizidine alkaloid, from Ficus hispida Linn. - Yap, V.A.; Loong, B.J.; Ting, K.N.; Loh, S.H.S.; Yong, Kien Thai; Low, Yun Yee; Kam, Toh Seok; Lim, K.H. (Elsevier, 2015)
Hispidacine, an 8,4′-oxyneolignan featuring incorporation of an unusual 2-hydroxyethylamine moiety at C-7, and hispiloscine, a phenanthroindolizidine alkaloid, were isolated from the stem-bark and leaves of the Malaysian Ficus hispida Linn. Their structures were established by spectroscopic analysis. Hispidacine induced a moderate vasorelaxant activity in rat isolated aorta, while hispiloscine showed appreciable antiproliferative activities against MDA-MB-231, MCF-7, A549, HCT-116 and MRC-5 cell lines.